Welfare Approach untuk Indonesia Damai dan Sejahtera: Perspektif Kesejahteraan Sosial - Siti Napsiyah Ariefuzzaman (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2012)
Symptoms of social violence that characterized by widespread ﬁ ghting between teens, ﬁ ghting between villages, burning houses, or the bombing which tends to lead to acts of terrorism and radicalism is still rife in our society. Motives and the reasons are many and complex. Among these factors is triggered by religious fanaticism, group, ethnicity, and socioeconomic disparities due to the very closely related to poverty and underdevelopment. This paper describes a welfare approach as a complete strategic framework to end social violence and terrorism in Indonesia. Keywords: kekerasan sosial, radikalisme, jihad, terorisme, security approach, welfare approach.